PENGARUH PEMBERIAN MOTIVASI TERHADAP KINERJA KARYAWAN - Zamri Zamri; Nurmaysaroh Nurmaysaroh; Mhd. Ikhwanda Nawawi; Irwan Purnama Putra (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
This study aims to determine and analyze the effect of motivation on employee performance at PT Bank Syariah Mandiri offices. Data collection is descriptive. Samples taken as many as 33 employees. This study aims to determine the effect of motivation on employee performance both simultaneously and partially. The results of this study conclude that giving motivation partially does not have a significant effect on employee performance at PT. Bank Syariah Mandiri Sub-Branch Office of Tax Village, North Labuhanbatu Regency.